Mutations in target gene confers resistance to acetolactate synthase inhibitors in Echinochloa phyllopogon - Zhang, Lulu (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.